(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study evaluates the complex Nigerian immigrant experiences as depicted in Chimamanda Ngozi Adchie’s Americanah, employing Paul Gilroy’s post-colonial concept of Melancholia. It contrasts the initial aspirations that led many Nigerians to seek a life in the West against the harsh realities encountered in countries like the United States and those in Europe. The investigation explores the motivations behind the rising phenomenon known as the ‘Japa’ syndrome, characterised by a desperate desire to leave Nigeria for better opportunities amid ongoing systemic issues, including poor governance, economic instability and social unrest. Through a close reading of Adichie’s narratives, this study uncovers the intricate interplay of race, gender, and class that poses significant challenges for African immigrants. These narratives vividly illustrates the disillusionment experienced by individuals who often confront racism, stereotyping and economic pressure, revealing how these complexities hinder assimilation and success. Consequently, many immigrants grapple with profound feelings of isolation and diminished self-worth. By linking melancholia with the immigrant experience, this study argues that the emotional burdens stemming from cultural dislocation and identity crises, severely impact immigrants psychological well-being. When these challenges are viewed merely as migration side effects rather than fundamental issues, they can inflict lasting harm on cultural identities and self-perception. This reinforces the notion that the American dream remains elusive for many, obstructed by structural racism, economic barriers, and societal stereotypes. The study concludes that the harsh realities faced by Nigerian immigrants require a critical re-evaluation of the American Dream, revealing it as a potentially misleading narrative that overlooks the unique complexities of the immigrant experience.